Case Report: Identification of Mutations in LAMP2 in Two Chinese Infants With Danon Disease - Zhang, Luyan (Front Genet, 2021)
Danon disease (DD) is a monogenic lysosomal storage disorder characterized by cardiomyopathy, skeletal myopathy, and variable degrees of intellectual disability. It is caused by a deficiency of lysosomal-associated membrane protein 2 (LAMP2). Two unrelated boys who presented with severe hypertrophic cardiomyopathy and elevated levels of liver enzymes, and were diagnosed with Danon disease at a very young age, were investigated. One boy was diagnosed at 4 months old and died soon after; his mother also died of hypertrophic cardiomyopathy shortly after his birth. Another developed hypertrophic cardiomyopathy at 3 months old but reported no significant cardiovascular symptoms during more than 5 years follow-up. Genetic screening found compound variants of LAMP2 and MYH7 in both of them. This report highlights the clinical heterogeneity in DD. The timely identification of LAMP2 mutation plays a critical role in their treatment and family counseling.